Regulation of Amyloid Precursor Protein Catabolism Involves the Mitogen-Activated Protein Kinase Signal Transduction Pathway - Mills, Julia (J Neurosci, 1997)
Catabolic processing of the amyloid precursor protein (APP) is subject to regulatory control by protein kinases. We hypothesized that this regulation involves sequential activation of the enzymes mitogen-activated protein kinase kinase (MEK) and extracellular signal-regulated protein kinase (ERK). In the present investigation, we provide evidence that MEK is critically involved in regulating APP processing by both nerve growth factor and phorbol esters. Western blot analysis of the soluble N-terminal APP derivative APP(s)demonstrated that the synthetic MEK inhibitor PD 98059 antagonized nerve growth factor stimulation of both APP(s) production and ERK activation in PC12 cells. Moreover, PD 98059 inhibited phorbol ester stimulation of APP(s) production and activation of ERK in both human embryonic kidney cells and cortical neurons. Furthermore, overexpression of a kinase-inactive MEK mutant inhibited phorbol ester stimulation of APP secretion and activation of ERK in human embryonic kidney cell lines. Most important, PD 98059 antagonized phorbol ester-mediated inhibition of Aβ secretion from cells overexpressing human APP(695) carrying the “Swedish mutation.” Taken together, these data indicate that MEK and ERK may be critically involved in protein kinase C and nerve growth factor regulation of APP processing. The mitogen-activated protein kinase cascade may provide a novel target for altering catabolic processing of APP.